PERLINDUNGAN HUKUM TERHADAP PEKERJA UTSOURCING AVIATION SECURITY (AVSEC) DI BANDARA SUPADIO PONTIANAK BERDASARKAN PERATURAN PEMERINTAH NOMOR 35 TAHUN 2021 TENTANG PERJANJIAN KERJA WAKTU TERTENTU, ALIH DAYA, WAKTU KERJA DAN WAKTU ISTIRAHAT, DAN PEMUTUSAN HUBUNGAN KERJA - NIM. A1012181057, BARRY PRIMA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The outsourcing system imposed on workers causes problems because workers do not get legal protection and their rights. One of the rights of outsourced workers who do not receive legal protection is the absence of an increase in worker status in the career path because outsourced workers will not be appointed as permanent workers. This also happened to Aviation Security (Avsec) outsourcing workers at Pontianak Supadio Airport, where Avsec outsourcing workers at Pontianak Supadio Airport were recruited by PT. Angkasa Pura Solusi which is a subsidiary of PT. Angkasa Pura II (Persero) with a Certain Time Work Agreement (PKWT). In fact, Avsec outsourced workers at Pontianak's Supadio Airport do not get legal protection. The formulation of the problem in this study is: